Desensitization and Prevention of Antibody-Mediated Rejection in Vascularized Composite Allotransplantation by Syngeneic Hematopoietic Stem Cell Transplantation. Issue 4 (April 2018) - Wang, Howard D.; Fidder, Samuel A.J.; Miller, Devin T.; Furtmüller, Georg J.; Ahmadi, Ali R.; Nägele, Felix; Lopez, Joseph; Quan, Amy; Budihardjo, Joshua; Lough, Denver M.; Akpinarli, Burcu; Etra, Joanna W.; et al.
Abstract : Background: Candidates for vascularized composite allotransplantation (VCA) are frequently sensitized, putting them at risk for antibody-mediated rejection. Current desensitization strategies are imperfect and require a living-donor setting. Here we investigated the impact of sensitization on and the efficacy of a desensitization protocol utilizing syngeneic hematopoietic stem cell transplantation (HSCT) to prevent antibody-mediated rejection in VCA. Methods: Skin transplants from Dark Agouti to Lewis rats were performed for sensitization. Orthotopic hind limb transplants from Dark Agouti donors were performed to sensitized and nonsensitized recipients, and the animals were treated with either daily tacrolimus or no immunosuppression. A desensitization protocol consisting of total body irradiation, fludarabine, and syngeneic HSCT was applied to sensitized animals. Graft rejection was monitored by clinical assessment and histological analysis. Serum levels of donor-specific antibodies (DSA IgG) were measured using flow cytometry. Results: Sensitized recipients exhibited accelerated rejection by 5.5 ± 1.2 days without immunosuppression and 10.2 ± 3.6 days with daily tacrolimus compared with 8.7 ± 1.2 days and longer than 30 days in nonsensitized recipients, respectively. Serum levels of DSA IgG were markedly elevated (37.3 ± 3.34-fold from baseline) in sensitized recipients after VCA and correlated with histologic evidence of rejection and C4d deposition. Desensitization significantly reduced DSA compared with sensitized controls (2.6 ± 0.5-fold vs 6.0 ± 1.2-fold, P < 0.01) and along with daily tacrolimus led to improved VCA survival longer than 30 days without evidence of C4d deposition (n = 6). Conclusions: In summary, sensitization leads to accelerated rejection of VCA, and syngeneic HSCT combined with conventional immunosuppression effectively reduces DSA and improves allograft survival in sensitized rats. Abstract : The authors report on the success of a desensitization protocol to prevent antibody-mediated rejection for vascular composite allotransplantation. Syngeneic hematopoietic stem cell transplantation in combination with conventional immunosuppression improves graft survival in a sensitized hind-limb rat transplant model. Supplemental digital content is available in the text.